Communication Patterns and Human Bonding in Long Distance Relationships between Parents and Children in Medan City - Margolang, Arif Hamdani; Hendra, Yan; Priadi, Ribut (CV. Literasi Indonesia, 2024)
This study aims to explain the communication pattern and relationship between parents and children (human bonding) in a long-distance relationship between parents and children in Medan. Attachment theory is used to explain the dynamics of relationships. The research uses a qualitative approach with a case study method. The research resource persons were six pairs of parents and children and two triangulators: a psychologist and a coordinator of adolescent resilience development National Population and Family Planning Board or Badan Kependudukan dan Keluarga Berencana Nasional (BKKBN) North Sumatra Province. The results showed that human bonding communication in long-distance relationships between parents and children took place with limited communication intensity. Communication is dominated and controlled by parents. There are many restrictions on children, lack of support, limited freedom of expression, imbalances in communication, strict control, and authoritarian attitudes of parents. This leads to a lack of quality of relationship between parents and children. This condition occurs in the communication process that forms monopoly communication patterns (monopoly pattern communication) and unbalanced split communication patterns (unbalanced split pattern communication); the formation of human bonding in long-distance relationships between parents and children is based on emotional relationships. Communication techniques of parents to children tend to be coercive. The child must obey many things. Human bonding in a long-distance relationship creates a relationship that is not harmonious and makes children feel insecure (insecure attachment).